2016
DOI: 10.1016/j.atherosclerosis.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical carotid atherosclerosis and neurocognitive function in an urban population

Abstract: Background and aims Examine age, sex, race, and socioeconomic status as modifiers of the association between carotid intimal medial thickness (IMT) and neurocognitive performance in a socioeconomically diverse, biracial, urban, adult population. Methods Participants were 1,712 community-dwelling adults (45% men, 56% African-American, 38% below poverty threshold, aged 30-64 years) enrolled in the Healthy Aging in Neighborhoods of Diversity across the Life Span (HANDLS) study. Participants underwent initial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In the present study, subclinical atherosclerosis was not associated with NCI; however, participants with subclinical atherosclerosis showed significantly lower capacity for DR. This study and others 35,36 suggest that CMI thickness could be associated with neurocognitive impairment in PLWHIV.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, subclinical atherosclerosis was not associated with NCI; however, participants with subclinical atherosclerosis showed significantly lower capacity for DR. This study and others 35,36 suggest that CMI thickness could be associated with neurocognitive impairment in PLWHIV.…”
Section: Discussionsupporting
confidence: 64%
“…The literature search retrieved 6879 studies, of which 19 cross‐sectional and 15 longitudinal studies were included in this systematic review and meta‐analysis 15 , 22 , 23 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 (Figure S1 ). The studies included a total of 50 779 participants aged 45.3 to 78.0 years.…”
Section: Resultsmentioning
confidence: 99%
“…Adjusting for cardiovascular and lifestyle variables resulted in a change in effect estimate and loss of significance. However, previous studies have shown that atherosclerosis is independently associated with reduced cognitive performance, but these studies have used other neuropsychological tests and different definitions of atherosclerosis, or have failed to perform multiple adjustments [11,15,20,21,35,36]. The heterogeneity in available data complicates comparison between studies.…”
Section: Discussionmentioning
confidence: 99%